Microbiological and Physicochemical Properties of Legume-Based Yogurt Drink Formulated from Jack Bean (Canavalia ensiformis L.) Extract and Kidney Bean (Phaseolus vulgaris L.) Extract - Cantika Zaddana; Muhammad Rizal Martua Damanik; Budi Setiawan; Ekowati Handharyani (Journal of Health and Nutrition Research, 2026)
Yogurt is a fermented dairy product whose quality is largely governed by the metabolic activity of lactic acid bacteria (LAB). In recent years, the development of plant-based yogurt has gained attention as a strategy to diversify fermented products, particularly legumes. Jack bean and kidney bean are legumes rich in complex carbohydrates and proteins that may support LAB growth during fermentation. This study aimed to evaluate the microbiological and physicochemical properties of legume-based yogurt drinks from jack bean and kidney bean extracts. Yogurt drinks were fermented by Streptococcus thermophilus and Lactobacillus bulgaricus as starter cultures. The study employed a Completely Randomized Design with formulas which was divided of different ratio of jack bean extract and kidney bean extract (P1: 0%; P2: 80%:0%; P3: 0:80%; F1: 40%:40%; F2: 60%:20%; F3: 20%:60%). All formulations were evaluated for LAB viability, and the highest LAB formula count was analyzed for pH, lactic acid content, viscosity, solids-non-fat (SNF), and reducing sugar levels. The results showed that Formula 2 containing 60% jack bean extract and 20% kidney bean extract met all evaluated parameters of SNI 2981:2009 which exhibited the highest LAB viability with 10.70±0.09 log CFU/mL (p<0.05), exceeding the minimum requirement (≥7 log CFU/mL). This formulation showed a pH of 4.23±0.00, lactic acid content of 1.954±0.03%, viscosity of 5.139±0.05 cP, SNF content of 9.410±0.09%, and relatively low reducing sugar content (2.017±0.06%). These results suggest the combination of jack bean-kidney bean shows strong potential as raw materials for legume-based yogurt drinks with favorable microbiological viability and physicochemical properties.